P449 Autologous fat graft injection for the treatment of perianal fistulas in Crohn's disease: A systematic review and single-arm meta-analysis. (21st January 2022) - De Gregorio, M; Tiang, T; Lee, T; Stellingwerf, M E; Basnayake, C; Kamm, M A; Niewiadomski, O; Schulberg, J D; Wright, E K; Connell, W; Thompson, A J; D'Souza co-lead senior author, B; et al.
Abstract: Background: Perianal fistulas are a debilitating complication of Crohn's disease. Long-term fistula healing rates remain poor with a need for effective novel therapies. Autologous fat graft injections are hypothesised to promote healing through the regenerative effects of mesenchymal stem cells; however, its efficacy remains unclear. We herein evaluated the efficacy of autologous fat graft injections for the treatment of Crohn's perianal fistulas in a systematic review and meta-analysis. Methods: A systematic review using the PRISMA Statement guidelines was performed. Database searches of MEDLINE, Embase, and PubMed, and grey literature searches were completed from January 1 st, 2001, to August 2 nd, 2021. Included publications evaluated fat graft injections for the treatment of Crohn's perianal fistulas. Excluded studies assessed injection of in vitro expanded mesenchymal stem cells or anovaginal fistulas. Primary outcomes included rates of clinical healing, which was defined as the presence of non-draining fistula tract external openings, and closure, which was defined as complete closure of fistula tract external openings. The secondary outcome was pooled clinical healing or closure, assessed in a random effects meta-analysis across identified studies, excluding case reports. Results: A total of 1, 258 publications were identified, with 891 articles assessed for eligibility and 107 deemed relevant for paper review. Six studies met inclusion criteria for qualitative analysis, comprising four single-arm intervention trials and two case reports. A total of 51 patients received autologous fat graft injections for treatment of Crohn's perianal fistulas, with follow-up ranging from 3 to 12 months. Variable techniques and filtration kits were used to acquire and process the harvested fat, with further differences in tract preparation, graft volume, and adjunctive surgical techniques. Two studies evaluated clinical healing ( n = 20) which was achieved in 20% and 60% at 3 and 12 months, respectively. Four studies evaluated clinical closure ( n = 31) which was achieved in 100%, 83%, and 100% at 3, 6, and 12 months, respectively. Clinical healing or closure was achieved in 74% in the pooled meta-analysis (95% confidence interval: 0.57, 0.85), with moderate heterogeneity between studies (I 2 Statistic: 59%; Cochran's Q test: P -value < 0.05). See Figure 1. Conclusion: Autologous fat graft injections for the treatment of Crohn's perianal fistulas shows promising results as a novel therapy in this systematic review and meta-analysis. Limited efficacy data showed clinical healing or closure as early as 3 months, with 74% achieving clinical success up to 12 months. Further assessment in controlled matched studies is needed.